Negative electrode material, preparation method thereof, negative electrode plate and lithium ion battery
By using a combination of a three-dimensional porous network structure and a lithium-philic compound in the metal lithium anode material, the cycle life and safety problems of metal lithium anode materials in the prior art are solved, and higher energy density and cycle stability are achieved.
Patent Information
- Application Number
- CN202311413938.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The existing metal lithium anode materials have shortcomings in cycle life, safety, lithium dendrites growth and solid electrolyte interface layer stability, resulting in poor energy density and cycle stability.
Using a negative electrode material with a three-dimensional porous network structure, a conductive network from the outside to the inside is formed by dispersing lithium-philic compounds and metal lithium in the porous carbon of high specific surfaces, using the outer carbon layer of the aerogel, promoting uniform deposition of lithium and inhibiting the formation of lithium dendrites.
The rate performance and cyclic performance of composite metal lithium negative electrode are improved, safety and conductivity are enhanced, and the energy density and cyclic stability of lithium-ion batteries are improved.
Smart Images

Figure CN119905534A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a negative electrode material and a preparation method thereof, as well as a negative electrode plate and a lithium ion battery. Background Art
[0002] With the rapid development of large-scale energy storage technology, electric vehicles and various electronic devices, the energy density of existing commercial lithium-ion battery systems can no longer meet the growing demands in these fields.
[0003] The gram capacity of metallic lithium is 3860mAh / g, and it has the lowest electrode potential, which enables metallic lithium to be used as the negative electrode of the battery, and has an absolute advantage in improving the battery energy density. However, metallic lithium currently faces the following problems as a negative electrode: such as short cycle life, low safety, uncontrollable growth of lithium dendrites, formation of dead lithium, and unstable solid electrolyte interface layer. These problems will lead to low reversible capacity, low first coulomb efficiency, poor cycle stability, and poor rate performance.
[0004] At present, the main research direction in the industry is to use carrier materials as the loading matrix of metal lithium to prepare composite metal lithium negative electrodes, reduce local current density, and regulate lithium deposition to inhibit the growth of metal lithium dendrites. However, the current methods of using carrier materials to load metal lithium negative electrodes mainly include lithium hot melt method and lithium electrodeposition method. These two processes are complex, inefficient, and costly, making them difficult to prepare and apply on a large scale, so they have not been effectively broken through. Summary of the invention
[0005] The purpose of the present invention is to provide a negative electrode material and a preparation method thereof, a negative electrode plate and a lithium ion battery. The negative electrode material is a three-dimensional porous network structure, and lithium-philic compounds dispersed inside the negative electrode material induce uniform lithium deposition during the charge and discharge process, thereby improving the rate performance and cycle performance of the composite metal lithium negative electrode.
[0006] To this end, in a first aspect, an embodiment of the present invention provides a negative electrode material having a three-dimensional porous network structure, which is composed of high specific surface area porous carbon, a lithium-philic compound, metallic lithium and an aerogel outer carbon layer;
[0007] The lithium-philic compound and metallic lithium are dispersed in the voids and on the surface of the high specific surface area porous carbon; the high specific surface area porous carbon is combined with the lithium-philic compound to provide a substrate for the deposition of metallic lithium, and the lithium-philic compound is used as a lithium element nucleation site to induce uniform deposition of lithium, so that lithium ions are uniformly embedded in and extracted from the negative electrode material during the charge and discharge process, so as to inhibit the formation of lithium dendrites on the surface of the negative electrode material;
[0008] The aerogel outer carbon layer is coated on the outside of the high specific surface porous carbon, and part of the metallic lithium is dispersed in the aerogel outer carbon layer. The aerogel outer carbon layer and the high specific surface porous carbon dispersed with the lithium-philic compound and metallic lithium provide a conductive network from the outside to the inside to improve the conductivity of the negative electrode material.
[0009] Preferably, the metallic lithium is formed by immersion of liquid metal and induction of deposition by a lithiophilic compound;
[0010] The liquid metal lithium solution comprises: a mixed solution of metal lithium material, aromatic compound and ether organic solvent;
[0011] The metal lithium material comprises: a combination of one or more of metal lithium strips, metal lithium powder and metal lithium sheets;
[0012] The aromatic compound includes: biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene or anthracene derivatives or a combination of one or more thereof;
[0013] The ether solvent includes any one or more combinations of diethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, dimethoxymethane, ethylene oxide, and propylene oxide.
[0014] Preferably, the lithium-philic compound comprises: any one or more combinations of copper oxide, nano zinc oxide, nano zinc powder, and nano niobium oxide;
[0015] The specific surface area of the high specific surface porous carbon is 1500 to 2500 m 2 / g.
[0016] In a second aspect, an embodiment of the present invention provides a method for preparing the negative electrode material according to the first aspect, comprising:
[0017] The high specific surface area porous carbon and hexadecyltrimethylammonium bromide are uniformly mixed by ultrasonication in deionized water according to a required mass ratio, and the surface-treated high specific surface area porous carbon is obtained after vacuum filtration, washing and drying;
[0018] Ultrasonic dispersion of the lithium-philic compound in a solvent to obtain a uniform suspension, and then adding the surface-treated high specific surface area porous carbon to the suspension and continuing ultrasonication, and vacuum filtering, washing and drying to obtain a composite;
[0019] preparing an aerogel outer carbon layer on the outer layer of the composite by a gas phase polymerization method to obtain a composite material coated with an aerogel outer carbon layer;
[0020] Dissolving a metallic lithium material and an aromatic compound in an ether organic solvent in a desired mass ratio under an inert environment to obtain a liquid metallic lithium solution;
[0021] The composite material coated with the outer carbon layer of the aerogel is added to the liquid metal lithium solution, and stirred in an inert environment in a glove box to volatilize the solvent, thereby obtaining a negative electrode material.
[0022] Preferably, the mass ratio of the high specific surface area porous carbon to hexadecyltrimethylammonium bromide is (5-15):1; the specific surface area of the high specific surface area porous carbon is 1500-2500m 2 / g;
[0023] The ultrasonic mixing is carried out in an ultrasonic pulverizer, the ultrasonic power is 120-200W, and the ultrasonic time is 0.5-1h.
[0024] Preferably, the mass ratio of the high specific surface area porous carbon to the lithium-philic compound is (15-25):1;
[0025] The lithium-philic compound comprises any one or more combinations of copper oxide, nano zinc oxide, nano zinc powder, and nano niobium oxide;
[0026] The solvent is any one of ionized water, anhydrous ethanol, ethylene glycol or acetone.
[0027] Preferably, the metal lithium material comprises: a combination of one or more of metal lithium strips, metal lithium powder, and metal lithium sheets;
[0028] The aromatic compound includes: biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene or anthracene derivatives or a combination of one or more thereof;
[0029] The ether solvent includes: any one or more combinations of diethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, dimethoxymethane, ethylene oxide, and propylene oxide;
[0030] The mass ratio of the metallic lithium to the aromatic compound is 1:9-5:5;
[0031] The inert environment is a nitrogen environment or an argon environment.
[0032] Preferably, the gas phase polymerization method is specifically: using the oxidation catalysis of iron p-toluenesulfonate to polymerize the organic carbon source on the surface of the composite to form the outer carbon layer of the aerogel, and the specific steps include:
[0033] Dispersing the iron p-toluenesulfonate and the composite in an organic solvent according to a certain mass fraction to form a suspension, coating the suspension on a glass plate and drying it in an oven, transferring the dried material together with the glass plate to a cavity filled with pyrrole vapor for catalytic polymerization until the material becomes a composite material coated with a brown aerogel outer carbon layer;
[0034] The organic solvent comprises: a combination of one or more of n-butanol, ethanol, methanol and propanol; in the suspension, the mass fraction of the complex is 20% to 40%; the mass fraction of the iron p-toluenesulfonate is 0.2% to 0.8%; and the drying temperature of the oven is 70° C. to 85° C.
[0035] In a third aspect, an embodiment of the present invention provides a negative electrode plate, which includes: the negative electrode material described in the first aspect above, or includes the negative electrode material prepared by the preparation method described in the second aspect above.
[0036] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode plate described in the first aspect.
[0037] The composite metal lithium negative electrode material provided by the embodiment of the present invention is a three-dimensional porous network structure, in which the high specific surface area porous carbon combined with the lithium-philic compound can provide a good lithium deposition substrate. The lithium-philic compound can induce uniform lithium deposition as a lithium element nucleation site, so that lithium ions are uniformly embedded and released during the charging and discharging process, thereby inhibiting the formation of lithium dendrites on the surface of the composite metal lithium negative electrode material and improving the safety and cycle stability of the metal lithium negative electrode; the outer carbon layer of the aerogel and the internal high specific surface area porous carbon can provide a conductive network from the outside to the inside, thereby improving the conductivity of the composite metal lithium negative electrode, thereby improving the rate performance of the composite metal lithium negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 A flow chart of a method for preparing a negative electrode material provided in an embodiment of the present invention;
[0039] Figure 2 Schematic diagram of the preparation process of the negative electrode material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0041] The embodiment of the present invention provides a negative electrode material having a three-dimensional porous network structure, and is composed of high specific surface area porous carbon, a lithium-philic compound, metallic lithium and an aerogel outer carbon layer.
[0042] Among them, the lithium-philic compound and metallic lithium are dispersed in the voids and surface of the high specific surface area porous carbon; the high specific surface area porous carbon is combined with the lithium-philic compound to provide a substrate for the deposition of metallic lithium, and the lithium-philic compound is used as a lithium element nucleation site to induce uniform deposition of lithium, so that lithium ions are uniformly embedded in and extracted from the negative electrode material during the charge and discharge process, so as to inhibit the formation of lithium dendrites on the surface of the negative electrode material.
[0043] The outer carbon layer of the aerogel is coated on the outside of the high specific surface porous carbon, and a small amount of metallic lithium is dispersed in the outer carbon layer of the aerogel. The outer carbon layer of the aerogel and the high specific surface porous carbon dispersed with lithium-philic compounds and metallic lithium provide a conductive network from the outside to the inside to improve the conductivity of the negative electrode material.
[0044] The specific surface area of the high specific surface porous carbon used in the present invention is 1500-2500m 2 / g
[0045] The preparation method of the negative electrode material of the present invention is as follows Figure 1 As shown, including:
[0046] Step 110, ultrasonically mixing the high specific surface area porous carbon and cetyltrimethylammonium bromide in deionized water according to a required mass ratio, and obtaining the surface-treated high specific surface area porous carbon after vacuum filtration, washing and drying;
[0047] Specifically, the mass ratio of the high specific surface porous carbon to hexadecyltrimethylammonium bromide is (5-15):1; the specific surface area of the high specific surface porous carbon is 1500-2500m 2 / g.
[0048] The ultrasonic mixing is carried out in an ultrasonic pulverizer, the ultrasonic power is 120 to 200 W, and the ultrasonic time is 0.5 to 1 h.
[0049] The purpose of surface treatment of high specific surface area porous carbon with hexadecyltrimethylammonium bromide is to introduce hydroxyl and carboxyl functional groups, change the surface properties of the carbon material, and further enhance the adsorption of the porous carbon material to lithium-philic compounds, so that more lithium-philic compounds can remain on the porous carbon during subsequent filtration and washing.
[0050] Step 120, ultrasonically dispersing the lithium-philic compound in a solvent to obtain a uniform suspension, then adding the surface-treated high specific surface area porous carbon to the suspension and continuing ultrasonication, and obtaining a composite after vacuum filtration, washing and drying;
[0051] Specifically, the amount of the lithium-philic compound is added according to the mass ratio of the high specific surface area porous carbon to the lithium-philic compound of (15-25):1.
[0052] The lithium-philic compound includes any one or more combinations of copper oxide, nano zinc oxide, nano zinc powder, and nano niobium oxide.
[0053] The solvent is any one of ionized water, anhydrous ethanol, ethylene glycol or acetone.
[0054] Step 130, preparing an aerogel outer carbon layer on the outer layer of the composite by a gas phase polymerization method to obtain a composite material coated with an aerogel outer carbon layer;
[0055] The gas phase polymerization method uses the oxidation catalysis of iron p-toluenesulfonate to polymerize the organic carbon source on the surface of the composite to form an aerogel outer carbon layer. The specific steps include:
[0056] The iron p-toluenesulfonate and the composite are dispersed in an organic solvent according to a certain mass fraction to form a suspension, the suspension is coated on a glass plate and placed in an oven for drying, and the dried material and the glass plate are transferred to a cavity filled with pyrrole vapor for catalytic polymerization until the material becomes a composite material coated with a brown aerogel outer carbon layer;
[0057] The organic solvent includes: a combination of one or more of n-butanol, ethanol, methanol and propanol; in the suspension, the mass fraction of the complex is 20% to 40%; the mass fraction of iron p-toluenesulfonate is 0.2% to 0.8%; and the drying temperature of the oven is 70° C. to 85° C.
[0058] Step 140, dissolving the metallic lithium material and the aromatic compound in an ether organic solvent in a desired mass ratio under an inert environment to obtain a liquid metallic lithium solution;
[0059] The metallic lithium material includes: a combination of one or more of metallic lithium strips, metallic lithium powder and metallic lithium sheets.
[0060] The aromatic compound includes: biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene or anthracene derivatives or a combination of one or more thereof.
[0061] The ether solvents include: any one or more combinations of ethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, dimethoxymethane, ethylene oxide, and propylene oxide.
[0062] The mass ratio of metallic lithium to the aromatic compound is 1:9-5:5.
[0063] The inert environment is a nitrogen environment or an argon environment.
[0064] Step 150, adding the composite material coated with the outer carbon layer of the aerogel into a liquid metal lithium solution, stirring in an inert environment in a glove box to volatilize the solvent, and obtaining a negative electrode material.
[0065] The stirring speed is 500-1000 rpm, and the solvent is volatilized at room temperature through rapid stirring.
[0066] Metallic lithium is formed by immersion of liquid metal and induction of deposition by lithium-philic compounds. The lithium-philic compounds and metallic lithium are dispersed in the voids and surface of high specific surface area porous carbon. The aerogel outer carbon layer is coated on the outside of the high specific surface area porous carbon. A small amount of metallic lithium is dispersed in the aerogel outer carbon layer to form a three-dimensional porous network structure.
[0067] The negative electrode material prepared in the present invention can be used as a negative electrode plate of a lithium ion battery.
[0068] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only partial embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention. In addition, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0069] Example 1
[0070] This embodiment provides a method for preparing a negative electrode material, and the process is schematically shown as follows: Figure 2 shown.
[0071] Step 1: Take 5g of porous carbon and 0.5 hexadecyltrimethylammonium bromide and add them to 300mL of deionized water. Use an ultrasonic cell crusher to sonicate for 0.5h with an ultrasonic power of 140W to obtain a uniform dispersion. Then, vacuum filtration, washing and drying are performed to obtain the surface-treated porous carbon. The particle size of the porous carbon is 8μm and the specific surface area is 1750m 2 / g.
[0072] Step 2, take 0.25g of nano zinc powder and add it to 300mL of ethylene glycol, use an ultrasonic cell crusher to ultrasonicate for 0.6h, the ultrasonic power is 130W, and a uniform suspension is obtained, and then the high specific surface area porous carbon after surface treatment obtained in step 1 is added to the suspension and ultrasonicated for 0.5h, and after vacuum filtration, washing and drying, complex A is obtained.
[0073] Step 3, take 5g of the composite A obtained in step 2 and 0.05g of iron p-toluenesulfonate, add them to 19.95g of n-butanol, stir quickly to obtain a uniform suspension, apply the suspension on a clean glass plate, quickly dry it in an oven at 70°C, and then transfer it to a chamber filled with pyrrole vapor for gas phase polymerization to obtain a brown composite material A@C coated with an aerogel outer carbon layer.
[0074] Step 4: Add 50 g of ether and 8 g of naphthalene to 2 g of lithium metal flakes in a high-speed stirring tank, and stir for 8 min in a glove box filled with nitrogen to form a liquid lithium metal solution.
[0075] Step 5, adding the A@C composite material of step 3 into the liquid metal lithium solution of step 4, rapidly stirring at 800 rpm in a glove box filled with nitrogen, and volatilizing the solvent to obtain a composite metal lithium negative electrode material.
[0076] Example 2
[0077] Step 1: Take 15g of porous carbon and 1.5 hexadecyltrimethylammonium bromide and add them to 350mL of deionized water. Use an ultrasonic cell crusher to sonicate for 0.5h with an ultrasonic power of 140W to obtain a uniform dispersion. Then, vacuum filtration, washing and drying are performed to obtain the surface-treated porous carbon. The particle size of the porous carbon is 7.5μm and the specific surface area is 2000m 2 / g;
[0078] Step 2, add 0.75g of nano copper oxide to 400mL of anhydrous ethanol, use an ultrasonic cell crusher to sonicate for 0.5h, and the ultrasonic power is 140W to obtain a uniform suspension, then add the high specific surface area porous carbon after surface treatment in step 1 to the suspension and continue sonication for 0.5h, and obtain composite A after vacuum filtration, washing and drying;
[0079] Step 3, taking 10 g of the composite A obtained in step 2 and 0.4 g of iron p-toluenesulfonate, adding them to 39.6 anhydrous ethanol, stirring rapidly to obtain a uniform suspension, coating the suspension on a clean glass plate, rapidly drying it in an oven at 75° C., and then transferring it to a chamber filled with pyrrole vapor for gas phase polymerization to obtain a composite material A@C coated with an aerogel outer carbon layer and in a brown color;
[0080] Step 4, adding 40 g of tetrahydrofuran and 9 g of biphenyl to 1 g of lithium metal in a high-speed stirring tank, and stirring for 15 min in a glove box filled with nitrogen to form a liquid lithium metal solution;
[0081] Step 5, adding the A@C composite material of step 3 to the liquid metal lithium solution of step 4, rapidly stirring at 1000 rpm in a glove box filled with nitrogen, and then increasing the temperature to evaporate the solvent to obtain a composite metal lithium negative electrode material.
[0082] Example 3
[0083] Step 1: Take 3g of porous carbon and 0.3 hexadecyl trimethyl ammonium bromide and add them to 150mL of deionized water. Use an ultrasonic cell crusher to sonicate for 0.5h with an ultrasonic power of 160W to obtain a uniform dispersion. Then, vacuum filtration, washing and drying are performed to obtain the surface-treated porous carbon; wherein the particle size of the porous carbon is 8μm and the specific surface area is 2150m 2 / g;
[0084] Step 2, add 0.15g of nano zinc oxide to 300mL of ethylene glycol, use an ultrasonic cell crusher to sonicate for 0.6h, and the ultrasonic power is 120W to obtain a uniform suspension, then add the high specific surface area porous carbon after the surface treatment in step 1 to the suspension and continue sonication for 0.5h, and obtain composite A after vacuum filtration, washing and drying;
[0085] Step 3, taking 2.5 g of the composite A obtained in step 2 and 0.125 g of ferric p-toluenesulfonate, adding them to 9.875 g of methanol, stirring rapidly to obtain a uniform suspension, coating the suspension on a clean glass plate, drying rapidly in an oven at 75° C., and then transferring it to a chamber filled with pyrrole vapor for gas phase polymerization to obtain a composite material A@C coated with a brown aerogel outer carbon layer;
[0086] Step 4, adding 30 g of ethylene oxide and 0.5 g of biphenyl to 0.5 g of lithium metal sheet in a high-speed stirring tank, and stirring for 30 min in a glove box filled with nitrogen to form a liquid lithium metal solution;
[0087] Step 5, adding the A@C composite material of step 3 to the liquid metal lithium solution of step 4, rapidly stirring at 1500 rpm in a glove box filled with nitrogen, and then increasing the temperature to evaporate the solvent to obtain a composite metal lithium negative electrode material.
[0088] Comparative Example 1
[0089] Step 1: Take 3g of porous carbon and 0.3 hexadecyltrimethylammonium bromide and add them to 150mL of deionized water. Use an ultrasonic cell crusher to sonicate for 0.5h with an ultrasonic power of 120W to obtain a uniform dispersion. After vacuum filtration, washing and drying, the surface-treated porous carbon is obtained; wherein the particle size of the porous carbon is 8μm and the specific surface area is 2150m 2 / g;
[0090] Step 2, taking 2.5 g of the surface-treated porous carbon obtained in step 1 and 0.125 g of ferric p-toluenesulfonate, adding them to 9.875 g of methanol, stirring rapidly to obtain a uniform suspension, coating the suspension on a clean glass plate, drying rapidly in an oven at 75° C., and then transferring it to a chamber filled with pyrrole vapor for gas phase polymerization to obtain a brown carbon-coated porous carbon coated with an aerogel outer carbon layer;
[0091] Step 3, adding 30 g of ether and 0.5 g of biphenyl to 0.5 g of lithium metal sheet in a high-speed stirring tank, and stirring for 30 min in a glove box to form a liquid lithium metal solution;
[0092] Step 4: adding the carbon-coated porous carbon of step 2 to the liquid metal lithium solution of step 3 and rapidly stirring in a glove box to evaporate the solvent to obtain a composite metal lithium negative electrode material.
[0093] Comparative Example 2
[0094] Step 1: Take 6g of porous carbon and 0.6 hexadecyl trimethyl ammonium bromide and add them to 200mL of deionized water. Use an ultrasonic cell crusher to sonicate for 0.5h with an ultrasonic power of 160W to obtain a uniform dispersion. Then, vacuum filtration, washing and drying are performed to obtain the surface-treated porous carbon; wherein the particle size of the porous carbon is 8μm and the specific surface area is 2050m 2 / g;
[0095] Step 2, adding 30 g of methyl ether and 1.6 g of biphenyl to 0.4 g of lithium metal sheet in a high-speed stirring tank, and stirring for 30 min in a glove box to form a liquid lithium metal solution;
[0096] Step 3, adding the porous carbon after the surface treatment in step 1 to the liquid metal lithium solution in step 2, and rapidly stirring in a glove box to evaporate the solvent to obtain a composite metal lithium negative electrode material.
[0097] The negative electrode materials obtained from the above-mentioned embodiments and comparative examples were used as negative electrode active materials, and were mixed with the conductive agent Super P and the binder polyacrylic acid (PAA) in a mass ratio of 80:10:10 to obtain a negative electrode slurry. The negative electrode slurry was coated on the current collector copper foil using an automatic coating machine with a coating thickness of 110 μm, and the negative electrode sheet was obtained after drying. The commercial positive electrode lithium cobalt oxide (LCO) powder, the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 7:2:1 and fully ground, and then an appropriate amount of N-methylpyrrolidone (NMP) was added as a dispersant, and a uniform slurry was obtained after stirring at a constant speed for 10 hours. Then, the prepared slurry was evenly coated on a clean and flat Al foil with a scraper, and placed in a vacuum drying oven at 80°C for continuous drying for 12 hours to obtain a positive electrode sheet. The positive electrode shell, positive electrode sheet, diaphragm, electrolyte, negative electrode sheet, gasket, shrapnel and negative electrode shell were stacked and assembled in sequence to obtain a battery. Among them, the diaphragm uses a polyethylene (PE) base film, and the electrolyte is 1 mol / L LiPF6 with EC (ethylene carbonate): DMC (dimethyl carbonate): DEC (diethyl carbonate) added = 1:1:1 (volume ratio). After the battery is assembled, the battery is activated by cycling 3 cycles at a current density of 0.1C in the voltage range of 3.0 to 4.2V, and then cycling 500 cycles at a current density of 0.5C. The test results of the capacity retention rate and the first week coulomb efficiency of each embodiment and comparative example after 500 cycles at a current density rate of 0.5C are shown in Table 1.
[0098] First week coulomb efficiency 500-week capacity retention rate Example 1 90.61% 87.51% Example 2 89.11% 81.33% Example 3 91.05% 84.31% Comparative Example 1 86.39% 72.13% Comparative Example 2 85.56% 66.62%
[0099] Table 1
[0100] It can be seen from the above table:
[0101] Compared with Comparative Examples 1 and 2, the first-week coulombic efficiency and 500-week capacity retention rate of Examples 1-3 have obvious advantages, which shows that the three-dimensional porous network structure formed by the outer carbon layer of the aerogel and the internal high specific surface area porous carbon can provide a conductive network from the outside to the inside, improve the conductivity of the composite metal lithium negative electrode, and thus improve the rate performance of the composite metal lithium negative electrode. At the same time, the introduction of the lithium-philic compound with uniform distribution and appropriate density can further promote uniform lithium deposition, so that lithium ions are uniformly embedded and extracted during the charge and discharge process, thereby inhibiting the formation of lithium dendrites on the surface of the composite metal lithium negative electrode material and improving the safety and cycle stability of the metal lithium negative electrode.
[0102] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A negative electrode material, characterized in that: The negative electrode material presents a three-dimensional porous network structure, which is composed of high specific surface area porous carbon, lithium-philic compound, metallic lithium and aerogel outer carbon layer; The lithium-philic compound and metallic lithium are dispersed in the voids and on the surface of the high specific surface area porous carbon; the high specific surface area porous carbon is combined with the lithium-philic compound to provide a substrate for the deposition of metallic lithium, and the lithium-philic compound is used as a lithium element nucleation site to induce uniform deposition of lithium, so that lithium ions are uniformly embedded in and extracted from the negative electrode material during the charge and discharge process, so as to inhibit the formation of lithium dendrites on the surface of the negative electrode material; The aerogel outer carbon layer is coated on the outside of the high specific surface porous carbon, and part of the metallic lithium is dispersed in the aerogel outer carbon layer. The aerogel outer carbon layer and the high specific surface porous carbon dispersed with the lithium-philic compound and metallic lithium provide a conductive network from the outside to the inside to improve the conductivity of the negative electrode material.
2. The negative electrode material according to claim 1, characterized in that The metallic lithium is formed by immersion of liquid metal and induction of deposition by a lithiophilic compound; The liquid metal lithium solution comprises: a mixed solution of metal lithium material, aromatic compound and ether organic solvent; The metal lithium material comprises: a combination of one or more of metal lithium strips, metal lithium powder and metal lithium sheets; The aromatic compound includes: biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene or anthracene derivatives or a combination of one or more thereof; The ether solvent includes any one or more combinations of diethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, dimethoxymethane, ethylene oxide, and propylene oxide.
3. The negative electrode material according to claim 1, characterized in that The lithium-philic compound comprises any one or more combinations of copper oxide, nano zinc oxide, nano zinc powder, and nano niobium oxide; The specific surface area of the high specific surface porous carbon is 1500 to 2500 m 2 / g.
4. A method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: The method comprises: The high specific surface area porous carbon and hexadecyltrimethylammonium bromide are uniformly mixed by ultrasonication in deionized water according to a required mass ratio, and the surface-treated high specific surface area porous carbon is obtained after vacuum filtration, washing and drying; Ultrasonic dispersion of the lithium-philic compound in a solvent to obtain a uniform suspension, and then adding the surface-treated high specific surface area porous carbon to the suspension and continuing ultrasonication, and vacuum filtering, washing and drying to obtain a composite; preparing an aerogel outer carbon layer on the outer layer of the composite by a gas phase polymerization method to obtain a composite material coated with an aerogel outer carbon layer; Dissolving a metallic lithium material and an aromatic compound in an ether organic solvent in a desired mass ratio under an inert environment to obtain a liquid metallic lithium solution; The composite material coated with the outer carbon layer of the aerogel is added to the liquid metal lithium solution, and stirred in an inert environment in a glove box to volatilize the solvent, thereby obtaining a negative electrode material.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the high specific surface porous carbon to hexadecyltrimethylammonium bromide is (5-15):1; the specific surface area of the high specific surface porous carbon is 1500-2500m 2 / g; The ultrasonic mixing is carried out in an ultrasonic pulverizer, the ultrasonic power is 120-200W, and the ultrasonic time is 0.5-1h.
6. The preparation method according to claim 4, characterized in that: The mass ratio of the high specific surface area porous carbon to the lithium-philic compound is (15-25):1; The lithium-philic compound comprises any one or more combinations of copper oxide, nano zinc oxide, nano zinc powder, and nano niobium oxide; The solvent is any one of ionized water, anhydrous ethanol, ethylene glycol or acetone.
7. The preparation method according to claim 4, characterized in that: The metal lithium material comprises: a combination of one or more of metal lithium strips, metal lithium powder and metal lithium sheets; The aromatic compound includes: biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene or anthracene derivatives or a combination of one or more thereof; The ether solvent includes: any one or more combinations of diethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, dimethoxymethane, ethylene oxide, and propylene oxide; The mass ratio of the metallic lithium to the aromatic compound is 1:9-5:5; The inert environment is a nitrogen environment or an argon environment.
8. The preparation method according to claim 4, characterized in that: The gas phase polymerization method specifically comprises: using the oxidation catalysis of iron p-toluenesulfonate to polymerize the organic carbon source on the surface of the composite to form the outer carbon layer of the aerogel, and the specific steps include: Dispersing the iron p-toluenesulfonate and the composite in an organic solvent according to a certain mass fraction to form a suspension, coating the suspension on a glass plate and drying it in an oven, transferring the dried material together with the glass plate to a cavity filled with pyrrole vapor for catalytic polymerization until the material becomes a composite material coated with a brown aerogel outer carbon layer; The organic solvent comprises: a combination of one or more of n-butanol, ethanol, methanol and propanol; in the suspension, the mass fraction of the complex is 20% to 40%; the mass fraction of the iron p-toluenesulfonate is 0.2% to 0.8%; and the drying temperature of the oven is 70° C. to 85° C.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises: the negative electrode material described in any one of claims 1 to 3 above, or comprises the negative electrode material prepared by the preparation method described in any one of claims 4 to 8 above.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 9 above.
Citation Information
Patent Citations
Lithium element supplementing method for electrode of lithium ion battery
CN103943825A
Polymer-matrix composite film high in thermoelectric property and preparing method of polymer-matrix composite film
CN105219103A
Composite metal lithium negative electrode, preparation method thereof and lithium battery
CN111916682A
Porous carbon material as well as preparation method and application thereof
CN114447329A
Lithium-loving carbon nanofiber framework material of flexible lithium metal battery as well as preparation method and application of lithium-loving carbon nanofiber framework material
CN115020707A